NETWORKING 2012 Workshops International IFIP TC 6 Workshops, ETICS, HetsNets, and CompNets, Held at NETWORKING 2012, Prague, Czech Republic, May 25, 2012. Proceedings - Becvar, Zdenek; Bestak, Robert; Kencl, Lukas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of three workshops colocated with NETWORKING 2012, held in Prague, Czech Republic, in May 2012: the Workshop on Economics and Technologies for Inter-Carrier Services (ETICS 2012), the Workshop on Future Heterogeneous Network (HetsNets 2012), and the Workshop on Computing in Networks (CompNets 2012). The 21 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics addressing the main research efforts in the fields of network management, quality of services, heterogeneous networks, and analysis or modeling of networks.
Keywords: Computer science; Computer communication systems; Software engineering; Algorithms; Computer simulation; Management information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Management of Computing and Information Systems; Simulation and Modeling; Electronic books